2005
DOI: 10.1091/mbc.e05-06-0527
|View full text |Cite
|
Sign up to set email alerts
|

Pml39, a Novel Protein of the Nuclear Periphery Required for Nuclear Retention of Improper Messenger Ribonucleoparticles

Abstract: Using a genetic screen, we have identified a previously uncharacterized Saccharomyces cerevisiae open reading frame (renamed PML39) that displays a specific interaction with nucleoporins of the Nup84 complex. Localization of a Pml39-green fluorescent protein (GFP) fusion and two-hybrid studies revealed that Pml39 is mainly docked to a subset of nuclear pore complexes opposite to the nucleolus through interactions with Mlp1 and Mlp2. The absence of Pml39 leads to a specific leakage of unspliced mRNAs that is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(140 citation statements)
references
References 43 publications
11
129
0
Order By: Relevance
“…3C). This feature, along with the role of Mlp1p as a checkpoint for export competent messenger ribonucleoparticles (mRNPs) (Green et al 2003;Palancade et al 2005), leads us to believe that exported unspliced reporter mRNPs in mlp1Δ cells could be improperly packaged, leading to a decreased signal by virtue of NMD and/or other degradation pathways. Further studies are needed to confirm this.…”
Section: Deletion Of Genes Within Specific Gene Expression Processes mentioning
confidence: 99%
“…3C). This feature, along with the role of Mlp1p as a checkpoint for export competent messenger ribonucleoparticles (mRNPs) (Green et al 2003;Palancade et al 2005), leads us to believe that exported unspliced reporter mRNPs in mlp1Δ cells could be improperly packaged, leading to a decreased signal by virtue of NMD and/or other degradation pathways. Further studies are needed to confirm this.…”
Section: Deletion Of Genes Within Specific Gene Expression Processes mentioning
confidence: 99%
“…Later on it has been observed that pre-mRNAs/unspliced RNAs are retained in the nucleus, which is mediated by some splicing factors (Rutz and Seraphin, 2000;Dziembowski et al, 2004). Several studies also reported that unspliced mRNA is usually trapped by several components of nuclear pore complex (NPC) in the nucleus to prevent production of toxic polypeptides (Galy et al, 2004;Palancade et al, 2005;Lewis et al, 2007). This proposed 'perinuclear mRNP quality control' has been recently revealed, in which endoribonuclease Swt1p is probably recruited transiently to NPCs to mediate the initiation of degradations for trapped pre-mRNP/mRNP at the perinuclear region (Skružný et al, 2009).…”
Section: Aberrant 5' Cap Mrnpmentioning
confidence: 99%
“…The best characterized components of this surveillance system are the nuclear-pore-associated proteins Mlp1 and Mlp2 Galy et al, 2004;Grant et al, 2008;Green et al, 2003;Vinciguerra et al, 2005), the Mlp-bound downstream effector Pml39 (Palancade et al, 2005), the nucleoporin Nup60 (Galy et al, 2004;Lewis et al, 2007) and the NE protein Esc1 (Lewis et al, 2007). Mlp1, Mlp2 and Pml39 have been found to be involved in the retention of unspliced and malformed mRNPs at the nuclear periphery and to favor their degradation in the nucleus (Galy et al, 2004;Palancade et al, 2005;Vinciguerra et al, 2005). A current model proposes that mRNPs dock at the Mlp gate through direct interaction between the poly(A) + -binding protein Nab2 and Mlp1 Grant et al, 2008;Green et al, 2003;Vinciguerra et al, 2005).…”
Section: Npc Association Might Contribute To the Tight Functional Coumentioning
confidence: 99%
“…Mlp1, in association with Pml39, would in turn act as a selective filter that either guides export-competent mRNAs towards translocation through the NPC or retains faulty mRNPs. The perinuclear Esc1 and Nup60 components serve predominantly structural roles in this pathway, as Esc1 functions in the correct assembly of the NPC nuclear basket (Lewis et al, 2007), and Nup60 directly tethers Mlp1 and Mlp2 and, therefore, Pml39 at the nuclear pore (Feuerbach et al, 2002;Palancade et al, 2005). Notably, Esc1, Nup60, Mlp1 and Mlp2 are all required to anchor the SUMO protease Ulp1 to the NPC, and Ulp1 is required for efficient nuclear pre-mRNA retention, raising the possibility that Ulp1-mediated de-sumoylation of mRNP-bound proteins is involved in mRNA-export surveillance (Lewis et al, 2007).…”
Section: Npc Association Might Contribute To the Tight Functional Coumentioning
confidence: 99%